Association between fungal dysbiosis in the first 1 000 days of life and childhood diseases - a review of research progress - Xiaoyan ZHANG; Xiaochuan WANG; Borui LIU; Jing YANG; Xiaoyu GAO; Jiajin HU (Editorial Office of Chinese Journal of Public Health, 2024)
Bacteria, as the major component of the human microbiome, have been shown to play important physiological roles in human health and disease development. However, a growing body of research suggests that fungi, which make up less than 1% of the human microbiome, also have a significant impact on human health, particularly in early life. Fungal colonization is strongly associated with the onset of future childhood diseases such as infectious diseases, allergic diseases, and intestinal diseases. Factors influencing early life, such as mode of birth and use of antibiotics, may be involved in the development of related diseases by affecting fungal colonization, but more research is needed to summarize this. This article reviews the characteristics of the fungal composition in the first 1 000 days of life, the related factors influencing the colonization of the early life fungal community, and the association between fungal dysbiosis and childhood diseases, providing a reference for the prevention and control of related childhood diseases.